HUBUNGAN LAMA PENGGUNAAN KONTRASEPSI PIL KB DENGAN KEJADIAN HIPERTENSI PADA PASANGAN USIA SUBUR (IBU) DI WILAYAH KERJA PUSKEMSAS LAKAHANG KECAMATAN TABULAHAN KABUPATEN MAMASA: THE CORRELATION OF LONG CONTRACEPTION USE OF KB PILLS WITH THE EVENT OF HYPERTENSION IN COUPLES OF RELIABLE AGE (Mother) IN THE WORK AREA OF PUSKEMSAS LAKAHANG, TABULAHAN DISTRICT, MAMASA REGENCY - YULIANA D (STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2020)
One of the factors that influence HYPERTENSION is the duration of use of the contraceptive pill. The duration of the use of contraceptive pills is the time taken by the acceptor to prevent pregnancy by taking one type of contraceptive pill/tablet continuously for a long time. In Indonesia, the use of hormonal contraception is permitted for 3 years and only recently has it been recommended to use it for 5 years. The purpose of this study was to determine the relationship between the length of use of the contraceptive pill with the incidence of hypertension in couples of childbearing age (mother) in Lakahang Village, Lakahang Community Health Center, Tabulangan District, Mamasa Regency, West Sulawesi Province. from 20 May to 20 June 2016. Using descriptive analytic method with a cross sectional study approach with Accidental Sampling sampling technique with a sample of 48 patients in Lakahang Village during the study and according to the inclusion criteria: All couples of childbearing age ( Mother) who suffers from hypertension who has visited the Lakahang pustu, and is currently taking birth control pills for 2 years and is willing to be investigated, Couples of childbearing age (Mother) who suffer from hypertension with ideal body weight and who suffer from hypertension without other diseases n and age partners have no previous family history of hypertension. Data obtained by interview technique using a questionnaire. Data analysis was carried out with the results of the study showing that: there is a relationship between the length of use of the contraceptive pill with the incidence of hypertension in Lakahang Village with p value = 0.000 > = 0.05..